Fresno County Bar Association Luncheon with Justice Cruz Reynoso - Watkins, Howard::::::::: (1982)
Lenore Schreiber, Justice Cruz Reynoso, Fresno County Bar Association President Robert Oliver, Fresno County Bar Association President-Elect Doug Jensen at head table The Fresno Hilton signs on lectern